A kind of wooden fish stone multifunctional composite fiber and preparation method thereof
By introducing chemical fiber reinforced functional bodies and viscose functional bodies into the wood stone fiber, combining the mechanical stability of chemical fibers with the high comfort of viscose fibers, the shortcomings of existing fibers in terms of mechanical stability and comfort are solved, and a high functionality, stability and comfort of wood stone multifunctional composite fibers are achieved.
Patent Information
- Application Number
- CN202410149167.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-02
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-02-02
AI Technical Summary
The existing wood stone functional fibers have shortcomings in terms of mechanical stability and comfort, and their functionality is weak when combined with chemical fibers alone.
By introducing chemical fiber reinforced functional bodies, the outer layer is coated with viscose functional bodies, combining the mechanical stability of chemical fibers with the high comfort and high functional effects of viscose fibers, Muyushi multifunctional composite fibers are prepared.
It improves the overall functionality, stability and comfort of the fiber, has high energy, promotes blood circulation and health care functions, and has good market prospects.
Smart Images

Figure CN117947540B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of functional fiber materials, and in particular to a wooden fish stone multifunctional composite fiber and a preparation method thereof. Background Art
[0002] Textile fibers are mainly divided into natural fibers and chemical fibers. Viscose fiber is one of the earliest textile fibers to be industrially produced on a large scale among regenerated cellulose fibers. It is made of natural cellulose (such as cotton linters, wood, reeds, etc.) as raw materials. It is made into soluble cellulose xanthate through processes such as alkalization, aging, and yellowing, and then dissolved in dilute alkali solution to make viscose, which is made through wet spinning. Viscose fibers are divided into two types of viscose fibers: filament and staple. Viscose filament is also called rayon or viscose silk; viscose staple fibers are cotton-type, wool-type, and medium-long fibers. During the spinning process, viscose fibers have good spinnability. They can be spun purely, or blended or interwoven with other textile fibers in different proportions. They are widely used in the textile field. Viscose fibers have the characteristics of high hygroscopicity, good air permeability, good drape, smoothness, antistatic, easy dyeing, and degradability. They are widely used in the textile field.
[0003] Muyushi is a famous mineral in China. According to research, it was formed about 550 to 580 million years ago. It is a precious jade stone. Its origin is limited to the west side of Mount Tai, and it is listed as one of the three ancient profile specimens in the world, in the area of Manshou Mountain in Changqing District. The reserves are limited and extremely precious. Because its color, pattern and sound are similar to the wooden fish struck by monks chanting scriptures, it is called Muyushi. According to the identification of the National Geological Experimental Testing Center, the Chinese Academy of Preventive Medicine and other units, Muyushi contains a variety of trace elements and minerals necessary for the human body, such as strontium, selenium, zinc, iron, molybdenum, lithium, manganese, beryllium, zinc metasilicate, sodium metasilicate and other 26 elements. Zinc ion is the basis of high-activity sperm. It is related to more than 100 enzymes related to life and is an indispensable trace element for the formation of proteins and nucleic acids closely related to memory. Zinc has anti-disease effects on aging, hypertension, diabetes, coronary heart disease, etc. Strontium is a component of human bones and teeth. Clinically, strontium has been found to reduce the incidence of cardiovascular diseases. Silicon in the form of metasilicic acid has health benefits for cardiovascular, stomach, and bone growth. The content of selenium in the human body is only a few milligrams. Selenium is one of the essential trace elements for the human body as determined by the World Health Organization. It has the function of scavenging free radicals. Free radicals are the source of all diseases. The accumulation of free radicals in the human body causes low immunity, arteriosclerosis, cancer, accelerated aging, and all kinds of diseases. Because selenium has the function of scavenging free radicals, it is praised by scientists as the "king of anti-cancer" and "the fire of life". Selenium deficiency can increase the incidence of cancer, especially cancers and leukemia in the prostate, breast, oocyte, lung and other parts, which are most related to selenium. Because the content of uranium and rare earth in wooden fish stone is moderate, it has good anti-corrosion and permeability.
[0004] Bianshi is called a magical stone, and also called a stone that can heal diseases. It is an extremely precious rock species with very few reserves. It is a microcrystalline limestone, and its main chemical component is calcium carbonate. The main component of Bianshi is microcrystalline limestone, and it contains more than 30 rare earth and trace elements such as strontium, titanium, chromium, manganese, and zinc that are beneficial to the human body. Bianshi can heal diseases, which has been recorded in ancient times and has been used for many years. Bianshi achieves some treatment and health care through the bands of microcrystalline infrared and pulses.
[0005] Medical stone is a natural medicinal ore, the main components of which are SiO2, Al2O3, CaO, MgO, Na2O2, K2O, Fe2O3, FeO, etc. In addition, it also contains trace elements such as Mn, P, Ba, Co, Cu, Zn, Sr, Mo, Ni, etc. It also contains all the major elements required by animals, such as K, Na, Ca, Mg, Cu, Mo, etc., among which Mn, Fe, Mo, P, Mg are anti-cancer elements. The trace elements contained in medical stone can improve the ability to resist fatigue, hypoxia and immunity, and have the effects of fitness, longevity, anti-aging and disease resistance. Its pharmacological effects and magical effects have long been recorded in the ancient Chinese medical masterpiece "Shennong's Herbal Classic". Since the 1960s, medical stone has been widely used abroad. The United States uses medical stone to make athlete drinks, Japan praises medical stone as "healthy medicinal stone", and South Korea calls it "mineral medicinal stone". It can be seen that people have recognized the biological activity and significant biological effects of medical stone.
[0006] With the development of science and technology and the improvement of living standards, people's requirements for quality of life are increasing day by day, and the demand for health preservation is also getting higher and higher. People are no longer satisfied with the single function of fiber textiles, but need more high-performance and multifunctional fiber textiles. The market potential of multifunctional fiber textiles is huge and has become a goal pursued by people. In the prior art, fibers made by adding minerals or other additives to fibers increase the characteristics and functions of fibers from different aspects. For example: Patent 200810157849.4 discloses wooden fish stone fiber and its preparation method and application; Patent 201610566698.2 discloses a health-care regenerated cellulose fiber containing Bian stone; 201810036122.4 discloses a far-infrared and negative ion multifunctional fabric; 201510999240 discloses a method for preparing viscose fiber containing medical stone. However, there are still many technical bottlenecks in the current wooden fish stone functional fibers. For example, the composite fiber prepared by blending viscose with wooden fish stone or medical stone still exhibits the functional defects of viscose fiber, such as easy deformation and poor mechanical stability; and simply combining chemical fiber with wooden fish stone functional fiber has problems of poor comfort and weak functionality. Therefore, by introducing chemical fiber reinforced functional body, covering the viscose functional body with the outer layer, using chemical fiber to provide mechanical stability, and using viscose material to provide high comfort and high functionality, the overall fiber functionality, stability and comfort can be improved without reducing the total content of wooden fish stone. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide a method for preparing a wooden fish stone multifunctional composite fiber. By introducing a chemical fiber reinforcement functional body and an outer layer covered with a viscose functional body, the high mechanical stability function of the chemical fiber and the high comfort and high functionality of the viscose fiber are successfully combined to develop a new wooden fish stone multifunctional composite fiber to improve the overall fiber functionality, stability and comfort.
[0008] Another object of the present invention is to provide a wooden fish stone multifunctional composite fiber prepared by the above method. The composite fiber of the present invention is applied to the field of health care, and can effectively combine the minerals wooden fish stone, Bian stone and medical stone and additives that are beneficial to the human body with textile fiber materials to prepare multifunctional composite fibers. The fiber of the present invention has high energy, can promote blood circulation, has health-preserving functions, has good market prospects, can effectively solve the problems raised by the background technology, and serves health.
[0009] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0010] A method for preparing a wooden fish stone multifunctional composite fiber, characterized by comprising the following steps:
[0011] (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water respectively, and then further clean and decompose them in sodium hydroxide solution with ultrasonic for 2 to 3 hours, repeat the process 1 to 3 times, and then dry them in a dryer;
[0012] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use;
[0013] (3) blending the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 20-35 parts of wooden fish stone, 10-20 parts of Bian stone, 4-10 parts of medical stone and 60-100 parts of chemical fiber polymer masterbatch;
[0014] (4) The fibers obtained by the blended melt spinning in step (3) are used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, and the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber;
[0015] (5) The fiber prepared in step (4) is cured by spraying water at room temperature for 2 to 4 hours, and then dried at 70 to 85° C. for 20 to 30 minutes to obtain the Muyushi multifunctional composite fiber.
[0016] Preferably, the chemical fiber polymer masterbatch in step (3) is one or a mixture of polypropylene, polyester, polylactic acid, polyethylene, polyurethane, polyvinyl chloride, polyvinylidene fluoride, and polyamide melt polymer masterbatch.
[0017] Preferably, the weight proportions of the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (3) are 22-33 parts of wooden fish stone, 11-19 parts of Bian stone, 5-9 parts of medical stone and 62-98 parts of chemical fiber polymer masterbatch.
[0018] Preferably, the weight proportions of the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (3) are 22 parts of wooden fish stone, 19 parts of Bian stone, 9 parts of medical stone and 98 parts of chemical fiber polymer masterbatch.
[0019] Preferably, the weight proportions of the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (3) are 33 parts of wooden fish stone, 11 parts of Bian stone, 8 parts of medical stone and 80 parts of chemical fiber polymer masterbatch.
[0020] Preferably, the weight proportions of the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (3) are 30 parts of wooden fish stone, 15 parts of Bian stone, 5 parts of medical stone and 62 parts of chemical fiber polymer masterbatch.
[0021] Preferably, the particle size of the chemical fiber polymer masterbatch described in step (3) is 100-500 mesh.
[0022] Preferably, the particle size of the chemical fiber polymer masterbatch described in step (3) is 100 mesh.
[0023] Preferably, the particle size of the chemical fiber polymer masterbatch described in step (3) is 300 mesh.
[0024] Preferably, the particle size of the chemical fiber polymer masterbatch described in step (3) is 500 mesh.
[0025] Preferably, the coating solution in step (4) comprises 10-15 parts of the wooden fish stone in step (2), 5-10 parts of the Bian stone, 2-5 parts of the medical stone, 0.5-2 parts of the coupling agent, 0.5-1.5 parts of the surfactant, and 100 parts of the viscose stock solution.
[0026] Preferably, the coating solution in step (4) comprises 11-14 parts of the wooden fish stone in step (2), 6-9 parts of Bian stone, 3-4 parts of medical stone, 0.6-1.8 parts of coupling agent, 0.6-1.4 parts of surfactant and 100 parts of viscose stock solution.
[0027] Preferably, the coating solution in step (4) comprises 11 parts of the wooden fish stone in step (2), 9 parts of Bian stone, 3 parts of medical stone, 1.0 part of coupling agent, 0.6 part of surfactant and 100 parts of viscose stock solution.
[0028] Preferably, the coating solution in step (4) comprises 12 parts of the wooden fish stone in step (2), 6 parts of Bian stone, 3.5 parts of medical stone, 0.6 parts of coupling agent, 1.4 parts of surfactant and 100 parts of viscose stock solution.
[0029] Preferably, the coating solution in step (4) comprises 14 parts of the wooden fish stone in step (2), 8 parts of Bian stone, 4 parts of medical stone, 1.8 parts of coupling agent, 0.9 parts of surfactant and 100 parts of viscose stock solution.
[0030] Preferably, the coupling agent described in step (4) is any one of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(β-methoxyethoxy)silane, KH550, KH560, and KH570.
[0031] Preferably, the surfactant in step (4) is an amine cationic surfactant, and the amine cationic surfactant is dialkyl dimethyl ammonium chloride or polyalkyl trimethyl ammonium chloride.
[0032] Preferably, in the coaxial wet spinning die described in step (4), the ratio of the die single spinneret aperture / core layer matrix fiber diameter is in the range of 1.5:1 to 8:1, and the maximum die size is 3 mm.
[0033] Preferably, in the coaxial wet spinning die described in step (4), the ratio of the die single spinneret aperture / core layer matrix fiber diameter is in the range of 1.5:1, and the maximum die size is 3 mm.
[0034] Preferably, in the coaxial wet spinning die described in step (4), the ratio of the die single spinneret aperture / core layer matrix fiber diameter is in the range of 3:1, and the maximum die size is 3 mm.
[0035] Preferably, in the coaxial wet spinning die described in step (4), the ratio of the die single spinneret aperture / core layer matrix fiber diameter is in the range of 8:1, and the maximum die size is 3 mm.
[0036] Preferably, in step (5), the product is sprayed with water for curing at room temperature for 3 hours, and then dried at 80°C for 25 minutes.
[0037] Preferably, in step (5), the product is sprayed with water for curing at room temperature for 2 hours, and then dried at 70° C. for 20 minutes.
[0038] Preferably, in step (5), the product is sprayed with water for curing at room temperature for 4 hours, and then dried at 85°C for 30 minutes.
[0039] A wooden fish stone multifunctional composite fiber is prepared by the method.
[0040] The multifunctional composite fiber product of the present invention has a wide range of applications, and can be specifically used in clothing, underwear, bedding, shoes and hats, socks and various protective gear.
[0041] The multifunctional composite fiber of the present invention is prepared by melt-wet composite technology, wherein the fiber obtained by blended melt spinning is the core fiber, which can provide stable support strength for the matrix fiber, and the wet coating layer fiber can provide comfort and moisture absorption function for the fiber.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] (1) The present invention provides a method for preparing a wooden fish stone multifunctional composite fiber. By introducing a chemical fiber reinforcement functional body and coating the outer layer with a viscose functional body, the high mechanical stability function of the chemical fiber and the high comfort and high functionality of the viscose fiber are successfully combined to develop a new wooden fish stone multifunctional composite fiber, thereby improving the overall fiber functionality, stability and comfort.
[0044] The multifunctional composite fiber of the present invention is prepared by melt-wet composite technology, wherein the fiber obtained by blended melt spinning is the core fiber, which can provide stable support strength for the matrix fiber, and the wet coating layer fiber can provide comfort and moisture absorption function for the fiber.
[0045] (2) The multifunctional composite fiber of wooden fish stone prepared by the present invention is applied in the field of health care. It can effectively combine the minerals wooden fish stone, Bian stone and medical stone and additives that are beneficial to the human body with textile fiber materials to prepare multifunctional composite fibers. The fiber of the present invention has high energy, can promote blood circulation, has health-preserving functions, has good market prospects, can effectively solve the problems raised by the background technology, and serve health.
[0046] (3) The fiber of the present invention is a new type of functional fiber. In addition to the advantages of viscose fiber such as being natural, spinnable, biodegradable, soft, and having excellent dyeing properties, it also has the mechanical stability and deformation resistance imparted by the chemical fiber matrix, and has excellent health care functions, multiple physiological activities and health care functions, thereby improving the quality of the material.
[0047] (4) The present invention improves the bonding strength between wooden fish stone, Bian stone, medical stone particles and the viscose system by adding a silane series coupling agent, thereby improving the quality of the fiber.
[0048] (5) The present invention adds a surfactant to make the wooden fish stone, Bian stone and medical stone powders have good compatibility and dispersibility, thereby improving the quality of the fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a surface SEM image of the Muyushi multifunctional composite fiber prepared in Example 1 of the present invention;
[0050] Figure 2 This is a surface SEM image of the Muyushi multifunctional composite fiber prepared in Example 2 of the present invention;
[0051] Figure 3 This is a surface SEM image of the Muyushi multifunctional composite fiber prepared in Example 3 of the present invention;
[0052] Figure 4 This is a surface SEM image of the Muyushi multifunctional composite fiber prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0053] The present invention will be further described below in conjunction with the accompanying drawings and Examples. It should be understood that these embodiments are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading content of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally. Example 1
[0054] The multifunctional composite fiber of Muyushi in this embodiment is prepared by the following steps:
[0055] (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water, then further clean and decompose them in sodium hydroxide solution with ultrasonic for 2 hours, repeat the process twice, and then dry them in a dryer;
[0056] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use;
[0057] (3) blending the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 20 parts of wooden fish stone, 20 parts of Bian stone, 10 parts of medical stone and 60 parts of chemical fiber polymer masterbatch; the chemical fiber polymer masterbatch is polypropylene; and the particle size of the chemical fiber polymer masterbatch is 100 mesh;
[0058] (4) The fiber obtained by the blended melt spinning in step (3) is used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, the ratio of the single spinneret aperture of the die head to the core layer fiber diameter is 8:1, the outer diameter size is 2 mm, and the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the specific weight parts are 10 parts of wooden fish stone, 10 parts of Bian stone, 2 parts of medical stone, 0.5 parts of coupling agent, 1.5 parts of surfactant, and 100 parts of viscose stock solution in step (2); the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber; the coupling agent is vinyl triethoxysilane; the surfactant is dialkyl dimethyl ammonium chloride;
[0059] (5) The fiber prepared in step (4) was sprayed with water for curing at room temperature for 4 hours, and then dried at 70° C. for 20 minutes to obtain the Muyushi multifunctional composite fiber.
[0060] Example 2
[0061] The multifunctional composite fiber of Muyushi in this embodiment is prepared by the following steps:
[0062] (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water, then further clean and decompose them in sodium hydroxide solution with ultrasonic for 3 hours, repeat the process 3 times, and then dry them in a dryer;
[0063] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use;
[0064] (3) blending the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 35 parts of wooden fish stone, 10 parts of Bian stone, 4 parts of medical stone and 100 parts of chemical fiber polymer masterbatch; the chemical fiber polymer masterbatch is polyester; and the particle size of the chemical fiber polymer masterbatch is 300 mesh;
[0065] (4) The fiber obtained by the blended melt spinning in step (3) is used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, the ratio of the single spinneret aperture of the die head to the core layer fiber diameter is 1.5:1, the outer diameter size is 2 mm, and the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the specific weight parts are 15 parts of wooden fish stone, 5 parts of Bian stone, 5 parts of medical stone and 2 parts of coupling agent, 0.5 parts of surfactant, and 100 parts of viscose stock solution in step (2); the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber; the coupling agent is vinyl trimethoxy silane; the surfactant is polyalkyl trimethyl ammonium chloride;
[0066] (5) The fiber prepared in step (4) was cured by spraying water at room temperature for 3 h, and then dried at 85° C. for 30 min to obtain the Muyushi multifunctional composite fiber.
[0067] Example 3
[0068] The multifunctional composite fiber of Muyushi in this embodiment is prepared by the following steps:
[0069] (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water respectively, and then further clean and decompose them in sodium hydroxide solution with ultrasonic for 2.5 hours, repeat the process 3 times, and then dry them in a dryer;
[0070] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use;
[0071] (3) blending the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 33 parts of wooden fish stone, 11 parts of Bian stone, 9 parts of medical stone and 98 parts of chemical fiber polymer masterbatch; the chemical fiber polymer masterbatch is polylactic acid; and the particle size of the chemical fiber polymer masterbatch is 150 mesh;
[0072] (4) The fiber obtained by the blended melt spinning in step (3) is used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, the ratio of the single spinneret aperture of the die head to the core layer fiber diameter is 3:1, the outer diameter size is 1 mm, and the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the specific weight parts are 11 parts of wooden fish stone, 9 parts of Bian stone, 3 parts of medical stone, 0.6 parts of coupling agent, 1.4 parts of surfactant, and 100 parts of viscose stock solution in step (2); the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber; the coupling agent is vinyl tri(β-methoxyethoxy) silane; the surfactant is dialkyl dimethyl ammonium chloride;
[0073] (5) The fiber prepared in step (4) was cured by spraying water at room temperature for 3 h, and then dried at 80° C. for 25 min to obtain the Muyushi multifunctional composite fiber.
[0074] Example 4
[0075] The multifunctional composite fiber of Muyushi in this embodiment is prepared by the following steps:
[0076] (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water, then further clean and decompose them in sodium hydroxide solution with ultrasonic for 2 hours, repeat the process twice, and then dry them in a dryer;
[0077] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use;
[0078] (3) blending the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 22 parts of wooden fish stone, 19 parts of Bian stone, 5 parts of medical stone and 62 parts of chemical fiber polymer masterbatch; the chemical fiber polymer masterbatch is polyethylene; and the particle size of the chemical fiber polymer masterbatch is 200 mesh;
[0079] (4) The fiber obtained by the blended melt spinning in step (3) is used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, the ratio of the single spinneret aperture of the die head to the core layer fiber diameter is 4:1, the outer diameter size is 1.5 mm, and the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the specific weight parts are 14 parts of wooden fish stone, 6 parts of Bian stone, 4 parts of medical stone, 1.8 parts of coupling agent, 0.6 parts of surfactant, and 100 parts of viscose stock solution in step (2); the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber; the coupling agent is KH550; the surfactant is polyalkyl trimethyl ammonium chloride;
[0080] (5) The fiber prepared in step (4) was cured by spraying water at room temperature for 2.5 h, and then dried at 75° C. for 28 min to obtain the Muyushi multifunctional composite fiber.
[0081] Example 5
[0082] The multifunctional composite fiber of Muyushi in this embodiment is prepared by the following steps:
[0083] (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water respectively, and then further clean and decompose them in sodium hydroxide solution with ultrasonic for 2.5 hours, repeat the process 3 times, and then dry them in a dryer;
[0084] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use;
[0085] (3) blending the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 25 parts of wooden fish stone, 18 parts of Bian stone, 8 parts of medical stone and 80 parts of chemical fiber polymer masterbatch; the chemical fiber polymer masterbatch is polyurethane; and the particle size of the chemical fiber polymer masterbatch is 180 mesh;
[0086] (4) The fiber obtained by the blended melt spinning in step (3) is used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, the ratio of the single spinneret aperture of the die head to the core layer fiber diameter is 5:1, the outer diameter size is 3 mm, and the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the specific weight parts are 18 parts of wooden fish stone, 7 parts of Bian stone, 4 parts of medical stone, 1.5 parts of coupling agent, 1.5 parts of surfactant, and 100 parts of viscose stock solution in step (2); the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber; the coupling agent is KH560; the surfactant is dialkyl dimethyl ammonium chloride;
[0087] (5) The fiber prepared in step (4) was cured by spraying water at room temperature for 3.5 hours, and then dried at 80° C. for 26 minutes to obtain the Muyushi multifunctional composite fiber.
[0088] Example 6
[0089] The multifunctional composite fiber of Muyushi in this embodiment is prepared by the following steps:
[0090] (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water, then further clean and decompose them in sodium hydroxide solution with ultrasonic for 3 hours, repeat the process once, and then dry them in a dryer;
[0091] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use;
[0092] (3) blending the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 20 parts of wooden fish stone, 16 parts of Bian stone, 10 parts of medical stone and 60 parts of chemical fiber polymer masterbatch; the chemical fiber polymer masterbatch is polyvinyl chloride; and the particle size of the chemical fiber polymer masterbatch is 190 mesh;
[0093] (4) The fiber obtained by the blended melt spinning in step (3) is used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, the ratio of the single spinneret aperture of the die head to the core layer fiber diameter is 5:1, the outer diameter size is 3 mm, and the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the specific weight parts are 10 parts of wooden fish stone, 8 parts of Bian stone, 3 parts of medical stone, 0.5 parts of coupling agent, 1.5 parts of surfactant, and 100 parts of viscose stock solution in step (2); the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber; the coupling agent is KH570; the surfactant is polyalkyl trimethyl ammonium chloride;
[0094] (5) The fiber prepared in step (4) was cured by spraying water at room temperature for 2 h, and then dried at 85° C. for 30 min to obtain the Muyushi multifunctional composite fiber.
[0095] Example 7
[0096] The multifunctional composite fiber of Muyushi in this embodiment is prepared by the following steps:
[0097] (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water respectively, and then further clean and decompose them in sodium hydroxide solution with ultrasonic for 2.6 hours, repeat the process twice, and then dry them in a dryer;
[0098] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use;
[0099] (3) blending the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 35 parts of wooden fish stone, 10 parts of Bian stone, 4 parts of medical stone and 60 parts of chemical fiber polymer masterbatch; the chemical fiber polymer masterbatch is polyvinylidene fluoride; and the particle size of the chemical fiber polymer masterbatch is 100 mesh;
[0100] (4) The fiber obtained by the blended melt spinning in step (3) is used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, the ratio of the single spinneret aperture of the die head to the core layer fiber diameter is 5:1, the outer diameter size is 2 mm, and the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the specific weight parts are 15 parts of wooden fish stone, 5 parts of Bian stone, 2 parts of medical stone, 0.8 parts of coupling agent, 1.2 parts of surfactant, and 100 parts of viscose stock solution in step (2); the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber; the coupling agent is vinyl triethoxysilane; the surfactant is dialkyl dimethyl ammonium chloride;
[0101] (5) The fiber prepared in step (4) was sprayed with water for curing at room temperature for 4 hours, and then dried at 70° C. for 20 minutes to obtain the Muyushi multifunctional composite fiber.
[0102] Example 8
[0103] The multifunctional composite fiber of Muyushi in this embodiment is prepared by the following steps:
[0104] (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water respectively, and then further clean and decompose them in sodium hydroxide solution with ultrasonic for 2 hours, repeat the process once, and then dry them in a dryer;
[0105] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use;
[0106] (3) blending the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 31 parts of wooden fish stone, 10 parts of Bian stone, 10 parts of medical stone and 90 parts of chemical fiber polymer masterbatch; the chemical fiber polymer masterbatch is a mixture of polypropylene and polyethylene; and the particle size of the chemical fiber polymer masterbatch is 220 mesh;
[0107] (4) The fiber obtained by the blended melt spinning in step (3) is used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, the ratio of the single spinneret aperture of the die head to the core layer fiber diameter is 7:1, the outer diameter size is 2 mm, and the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the specific weight parts are 13 parts of wooden fish stone, 8 parts of Bian stone, 5 parts of medical stone, 2 parts of coupling agent, 0.5 parts of surfactant, and 100 parts of viscose stock solution in step (2); the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber; the coupling agent is vinyl trimethoxy silane; the surfactant is polyalkyl trimethyl ammonium chloride;
[0108] (5) The fiber prepared in step (4) was cured by spraying water at room temperature for 4 hours, and then dried at 75° C. for 26 minutes to obtain the Muyushi multifunctional composite fiber.
[0109] Example 9
[0110] The multifunctional composite fiber of Muyushi in this embodiment is prepared by the following steps:
[0111] (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water respectively, and then further clean and decompose them in sodium hydroxide solution with ultrasonic for 2.8 hours, repeat the process twice, and then dry them in a dryer;
[0112] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use;
[0113] (3) blending the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 28 parts of wooden fish stone, 17 parts of Bian stone, 9 parts of medical stone and 75 parts of chemical fiber polymer masterbatch; the chemical fiber polymer masterbatch is polyamide; and the particle size of the chemical fiber polymer masterbatch is 160 mesh;
[0114] (4) The fiber obtained by the blended melt spinning in step (3) is used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, the ratio of the single spinneret aperture of the die head to the core layer fiber diameter is 4:1, the outer diameter size is 2 mm, and the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the specific weight parts are 15 parts of wooden fish stone, 5 parts of Bian stone, 35 parts of medical stone, 0.5 parts of coupling agent, 1.3 parts of surfactant, and 100 parts of viscose stock solution in step (2); the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber; the coupling agent is vinyl tri(β-methoxyethoxy) silane; the surfactant is dialkyl dimethyl ammonium chloride;
[0115] (5) The fiber prepared in step (4) was cured by spraying water at room temperature for 2.8 h, and then dried at 78° C. for 28 min to obtain the Muyushi multifunctional composite fiber.
[0116] Example 10
[0117] The multifunctional composite fiber of Muyushi in this embodiment is prepared by the following steps:
[0118] (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water, then further clean and decompose them in sodium hydroxide solution with ultrasonic for 2.4 hours, repeat the process once, and then dry them in a dryer;
[0119] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use;
[0120] (3) blending the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 26 parts of wooden fish stone, 15 parts of Bian stone, 6 parts of medical stone and 100 parts of chemical fiber polymer masterbatch; the chemical fiber polymer masterbatch is polylactic acid; and the particle size of the chemical fiber polymer masterbatch is 240 mesh;
[0121] (4) The fiber obtained by the blended melt spinning in step (3) is used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, the ratio of the single spinneret aperture of the die head to the core layer fiber diameter is 4:1, the outer diameter size is 2 mm, and the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the specific weight parts are 12 parts of wooden fish stone, 7 parts of Bian stone, 3 parts of medical stone, 0.9 parts of coupling agent, 0.8 parts of surfactant, and 100 parts of viscose stock solution in step (2); the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber; the coupling agent is KH550; the surfactant is dialkyl dimethyl ammonium chloride;
[0122] (5) The fiber prepared in step (4) was cured by spraying water at room temperature for 2 h, and then dried at 85° C. for 30 min to obtain the Muyushi multifunctional composite fiber.
[0123] Embodiment 11
[0124] The multifunctional composite fiber of Muyushi in this embodiment is prepared by the following steps:
[0125] (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water, then further clean and decompose them in sodium hydroxide solution with ultrasonic for 2 hours, repeat the process twice, and then dry them in a dryer;
[0126] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use;
[0127] (3) blending the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 22 parts of wooden fish stone, 18 parts of Bian stone, 10 parts of medical stone and 62 parts of chemical fiber polymer masterbatch; the chemical fiber polymer masterbatch is polyethylene; and the particle size of the chemical fiber polymer masterbatch is 170 mesh;
[0128] (4) The fiber obtained by the blended melt spinning in step (3) is used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, the ratio of the single spinneret aperture of the die head to the core layer fiber diameter is 4:1, the outer diameter size is 2 mm, and the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the specific weight parts are 13 parts of wooden fish stone, 7 parts of Bian stone, 2 parts of medical stone, 0.5 parts of coupling agent, 1.5 parts of surfactant, and 100 parts of viscose stock solution in step (2); the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber; the coupling agent is KH560; the surfactant is dialkyl dimethyl ammonium chloride;
[0129] (5) The fiber prepared in step (4) was cured by spraying water at room temperature for 4 hours, and then dried at 85° C. for 20 minutes to obtain the Muyushi multifunctional composite fiber.
[0130] Example 12
[0131] The multifunctional composite fiber of Muyushi in this embodiment is prepared by the following steps:
[0132] (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water, then further clean and decompose them in sodium hydroxide solution with ultrasonic for 2.9 hours, repeat the process 3 times, and then dry them in a dryer;
[0133] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use;
[0134] (3) blending the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 33 parts of wooden fish stone, 11 parts of Bian stone, 5 parts of medical stone and 62 parts of chemical fiber polymer masterbatch; the chemical fiber polymer masterbatch is a mixture of polyurethane and polyvinyl chloride; the particle size of the chemical fiber polymer masterbatch is 190 mesh;
[0135] (4) The fiber obtained by the blended melt spinning in step (3) is used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, the ratio of the single spinneret aperture of the die head to the core layer fiber diameter is 3:1, the outer diameter size is 2 mm, and the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the specific weight parts are 11 parts of wooden fish stone, 7 parts of Bian stone, 5 parts of medical stone, 2 parts of coupling agent, 0.8 parts of surfactant, and 100 parts of viscose stock solution in step (2); the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber; the coupling agent is KH570; the surfactant is polyalkyl trimethyl ammonium chloride;
[0136] (5) The fiber prepared in step (4) was cured by spraying water at room temperature for 4 hours, and then dried at 80° C. for 25 minutes to obtain the Muyushi multifunctional composite fiber.
[0137] Example 13
[0138] The multifunctional composite fiber of Muyushi in this embodiment is prepared by the following steps:
[0139] (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water, then further clean and decompose them in sodium hydroxide solution with ultrasonic for 3 hours, repeat the process 3 times, and then dry them in a dryer;
[0140] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use;
[0141] (3) blending the wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 22 parts of wooden fish stone, 11 parts of Bian stone, 8 parts of medical stone and 95 parts of chemical fiber polymer masterbatch; the chemical fiber polymer masterbatch is polyvinylidene fluoride; and the particle size of the chemical fiber polymer masterbatch is 140 mesh;
[0142] (4) The fiber obtained by the blended melt spinning in step (3) is used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, the ratio of the single spinneret aperture of the die head to the core layer fiber diameter is 3:1, the outer diameter size is 2 mm, and the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the specific weight parts are 12 parts of wooden fish stone, 7 parts of Bian stone, 3 parts of medical stone, 0.7 parts of coupling agent, 1.1 parts of surfactant, and 100 parts of viscose stock solution in step (2); the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber; the coupling agent is vinyl triethoxysilane; the surfactant is dialkyl dimethyl ammonium chloride;
[0143] (5) The fiber prepared in step (4) was sprayed with water for curing at room temperature for 3 hours, and then dried at 70° C. for 20 minutes to obtain the Muyushi multifunctional composite fiber.
[0144] Comparative Example 1
[0145] (1) Rinse the wooden fish stone, Bian stone and medical stone separately with clean water, then further clean and decompose them in sodium hydroxide solution with ultrasonic for 3 hours, repeat the process 3 times, and then dry them in a dryer;
[0146] (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for later use;
[0147] (3) Blending wooden fish stone, Bian stone, medical stone and chemical fiber polymer masterbatch for melt spinning, wherein the specific weight parts are 30 parts of wooden fish stone, 20 parts of Bian stone, 8 parts of medical stone and 80 parts of polypropylene; screw extrusion → pre-filtration → spinning to obtain matrix chemical functional fiber;
[0148] (4) The fiber prepared in step (3) was sprayed with water for curing at room temperature for 3 hours, and then dried at 85° C. for 30 minutes to obtain the Muyushi multifunctional composite fiber.
[0149] Comparative Example 2
[0150] (1) Single-hole wet spinning was performed directly on 100% viscose stock solution, the spinneret hole size was 2 mm, and the coagulation bath was a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate;
[0151] (2) Curing the fiber prepared in step (1) by spraying water at room temperature for 2 hours; then drying at 80° C. for 25 minutes to obtain fiber.
[0152] The specific method of promoting the blood circulation function of the Muyushi multifunctional composite fiber is to use a thermal infrared imager to perform thermal imaging tests on the skin blood microcirculation of the textiles prepared using the fibers of the embodiment and the comparative example, and to evaluate the effect of the functional fiber on the blood flow by comparing the temperature changes of the infrared thermal map of the test area. The greater the blood flow in the test area, the higher the temperature of the area, and the more obvious the hot zone on the infrared thermal map, that is, the more obvious the blood circulation promotion effect of the functional fiber.
[0153]
[0154] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a multifunctional composite fiber of wooden fish stone, characterized in that: The following steps are involved: (1) Rinse the wooden fish stone, Bian stone and medical stone with clean water respectively, and then further clean and decompose them in sodium hydroxide solution with ultrasonic for 2 to 3 hours, repeat the process 1 to 3 times, and then dry them in a dryer; (2) Use a grinder to grind the wooden fish stone, Bian stone and medical stone into particles with a diameter less than 1 μm, and store them separately for future use; (3) blending the wooden fish stone, Bian stone, medical stone and polylactic acid polymer masterbatch in step (2) for melt spinning, wherein the specific weight parts are 20-35 parts of wooden fish stone, 10-20 parts of Bian stone, 4-10 parts of medical stone and 60-100 parts of polylactic acid polymer masterbatch; (4) The fibers obtained by the blended melt spinning in step (3) are used as the core layer matrix online, introduced into a coaxial wet spinning die head, and coaxial wet spinning is performed, wherein the coagulation bath is a mixed bath of sulfuric acid, sodium sulfate and zinc sulfate; the coating layer solution outside the core layer matrix is a mixed spinning solution of viscose and wooden fish stone, Bian stone, medical stone, coupling agent and surfactant; the core layer matrix can provide stable support strength for the matrix fiber, and the coating layer can provide comfort and moisture absorption function for the fiber; the coaxial wet spinning die head, wherein the ratio of the die head single spinneret aperture / core layer matrix fiber diameter ranges from 1.5:1 to 8:1, and the maximum die head size is 3 mm; (5) The fiber prepared in step (4) is cured by spraying water at room temperature for 2 to 4 hours, and then dried at 70 to 85° C. for 20 to 30 minutes to obtain the Muyushi multifunctional composite fiber.
2. The method for preparing a MUYUSHI multifunctional composite fiber according to claim 1, characterized in that: The particle size of the polylactic acid polymer masterbatch described in step (3) is 100 to 500 meshes.
3. The method for preparing a MUYUSHI multifunctional composite fiber according to claim 1, characterized in that: The coating solution in step (4) specifically comprises 10-15 parts of the wooden fish stone in step (2), 5-10 parts of the Bian stone, 2-5 parts of the medical stone, 0.5-2 parts of the coupling agent, 0.5-1.5 parts of the surfactant, and 100 parts of the viscose stock solution.
4. The method for preparing a MUYUSHI multifunctional composite fiber according to claim 1, characterized in that: The coupling agent described in step (4) is any one of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(β-methoxyethoxy)silane, KH550, KH560, and KH570.
5. The method for preparing a MUYUSHI multifunctional composite fiber according to claim 1, characterized in that: The surfactant described in step (4) is an amine cationic surfactant, and the amine cationic surfactant is dialkyl dimethyl ammonium chloride or polyalkyl trimethyl ammonium chloride.
6. A multifunctional composite fiber of wooden fish stone, characterized in that: It is prepared by the method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Wooden fish stone fiber and preparation method and application thereof
CN101724930A
Stone needle-containing healthcare regenerated cellulose fiber and preparation method thereof
CN105970327A
Multifunctional fabric capable of releasing far infrared rays and anions
CN108301237A
Preparation method and application of crystal fiber
CN109537103A
Polytetrafluoroethylene-based sheath core composite fiber and production thereof
JP1998273826A